FACIAL BURNS: PROBLEMS AND MANAGEMENT - S. K. ACHARYA (Indian Journal of Plastic Surgery)
Facial burn injuries in majority of cases result in cosmetic disfigurement and functional disability. Cariful assessment, judiciously planned treatment, executed with skill and expediency, minimise such sequelae. Experience of managing one hundred and four cases of facial burns are presented. The importance of conservative regime in burns of first degree and well tried reconstructive procedures for second and third degree burns needs to be appreciated.